Splićani - Croati a cavallo u mletačkim prekojadranskim kopnenim postrojbama u 18. stoljeću - Čoralić, Lovorka (2020)
Središnje istraživačko zanimanje ovoga rada usmjereno je na proučavanje udjela Splićana u profesionalnoj mletačkoj konjaničkoj postrojbi (Croati a cavallo, Cavalleria Croati) tijekom 18. stoljeća. Rad se zasniva na istraživanju gradiva iz Archivio di Stato di Venezia (fond: Inquisitori sopra l'amministrazione dei pubblici ruoli). Na osnovi navedenoga gradiva, kao i postojećih spoznaja iz historiografije, analizira se vremenski okvir djelovanja Splićana u rečenoj postrojbi, način njihova bilježenja, trajanje vojne službe, udio pripadnika iz istih obitelji, osobne (tjelesne) značajke vojnika, kao i mjesto njihova popisivanja te zapovjedni kadar jedinica u kojima su bili prisutni. Zaključak rada jest da su Splićani činili vrlo zapažen dio hrvatskoga konjaništva pod stijegom Serenissime te da ovdje provedena raščlamba teži pridonijeti boljemu poznavanju vojne povijesti Dalmacije (u konkretnome slučaju grada Splita) i Mletačke Republike u posljednjemu stoljeću njihova opstojanja u zajedničkoj državi.
As part of the study of the military history of Dalmatia and the Venetian Republic through several centuries of existence in a common state union, the share of Croats in the Venetian military forces has been assessed as extremely significant. Operating as the local (territorial) units, as well as members of professional forces (Fanti oltramarini – infantry; Croati a cavallo, Cavalleria Croati – cavalry), soldiers from Dalmatia made a notable contribution to the preservation of Venetian territorial acquisitions from Veneto (terraferma) to the south of the eastern Adriatic coast. Investigation of this issue is complex and requires an analysis of documents stored in the Archivio di Stato di Venezia and the State Archive in Zadar, as well as other Croatian and international archival institutions and libraries. Following several years of research on this issue, this paper focuses on the role of Spalatans in the Croatian cavalry under the standard of St Mark in the 18th century, and is based on an analysis of sources from the collection of Inquisitori sopra l’amministrazione dei pubblici ruoli in the central Venetian state archives. Based on the said documents, as well as previous historiographical insights, the author focuses on the time frame of the Spalatans’ participation in the abovementioned cavalry unit, the method of their documentation, the duration of military service, the share of members from the same families, personal (physical) features of soldiers, the location of their documentation, and the command staff of the units in which they operated. The presence of Spalatans in Venetian cavalry can been observed throughout the century, while the places of their activity (documentation) reflect the distribution of Venetian acquisitions from the terraferma through Dalmatia and the Bay of Kotor to Greece, also testifying to the mobility of elite Venetian land units.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 247-248.
Sažetak ; Summary.
Keywords: Vojna povijest -- Konjaničke postrojbe; 18. st; Split -- Dalmacija -- Mletačka Republika